Emotional Maturity in Marriage: A Literature Review - A Munawara Azzahra; Haerani Nur (Universitas Negeri Gorontalo, 2025)
Abstract This study aims to explore the relationship between emotional maturity and marital quality through a systematic review of 30 selected scientific articles. The findings reveal that emotional maturity positively correlates with marriage readiness, relationship harmony, marital adjustment, conflict management, and marital satisfaction. Furthermore, emotional maturity is influenced by factors such as family background, mental health, education, age, and premarital experiences. Interventions such as communication skills training, cognitive-behavioral training, and premarital counseling have been shown to be effective in enhancing emotional maturity among couples. These findings highlight the critical role of emotional maturity in building healthy and sustainable marital relationships and provide recommendations for developing more systematic premarital intervention programs. Future research is encouraged to adopt longitudinal approaches and to consider more diverse cultural and gender contexts. Keywords: emotional maturity, marriage readiness, marital satisfaction, marital adjustment, marital conflict